2023
DOI: 10.3389/fcomm.2023.1035593
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the moderating role of information seeking platforms on university students' risk perception and anxiety during the COVID-19 pandemic in Ghana

Abstract: IntroductionThe emergence of COVID-19 resulted in heightened usage of online information seeking platforms among students aimed at obtaining information about the virus. This situation further increased the levels of risk perception and anxiety levels as students managed to stay safe. This study examined the roles of information seeking platforms; specifically, social media platforms and professional platforms as moderators of the link between risk perception and anxiety among university students in Ghana.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Such students have gone through 3 years of tertiary education either at the training college or technical university ( 81 ). Previous studies conducted in this same university have revealed a similar population distribution in terms of age ( 82 , 83 ). Besides, the convenient sampling approach adopted could have skewed the sample to include these students with diploma degree qualification.…”
Section: Methodssupporting
confidence: 61%
“…Such students have gone through 3 years of tertiary education either at the training college or technical university ( 81 ). Previous studies conducted in this same university have revealed a similar population distribution in terms of age ( 82 , 83 ). Besides, the convenient sampling approach adopted could have skewed the sample to include these students with diploma degree qualification.…”
Section: Methodssupporting
confidence: 61%
“…The outbreak of the virus led to an infrastructure and digital divide among schools and individuals in Ghana [1]. This gap increased the demands/workloads on teachers and students, causing psychological consequences such as depression, anxiety, stress, fear, and panic [42][43][44][45]. Previous studies in Ghana revealed that both teachers and students perceived their school environment to be unsafe during the pandemic [4,12,16].…”
Section: Introductionmentioning
confidence: 99%
“…University students in Ghana can be regarded as a vulnerable group as they face challenging circumstances and new experiences in their life course and this makes them susceptible to mental health problems [30][31][32][33][34][35][36] and this could affect their SWB. This could be worsened by the current economic hardship in the country.…”
Section: Introductionmentioning
confidence: 99%